Dark Territory : The Secret History of Cyber War - Kaplan , Fred (Zurich ISN-ETH Zurich, 2016)
In this video, Fred Kaplan discusses his new book, "Dark Territory," which focuses on the untold story of the officers, policymakers, scientists, and spies who created cyber warfare and who have been planning and engaging in this type of conflict for decades now.
Licencia estandar Youtube
Keywords: Seguridad; Delitos informáticos